Occurrence and Exposure Assessment of Rare Earth Elements in Zhejiang Province, China - Shufeng Ye; Ronghua Zhang; Pinggu Wu; Dong Zhao; Jiang Chen; Xiaodong Pan; Jikai Wang; Hexiang Zhang; Xiaojuan Qi; Qin Weng; Zijie Lu; Biao Zhou (Foods)
In this study, we aimed to investigate the occurrence of rare earth elements (REEs) in commonly consumed foods and assess the dietary exposure risks among different age groups in Zhejiang Province. The results showed that tea and shrimp had the highest REE detection rates, reaching 100%. Of all the food categories examined, tea exhibited the highest REE concentrations, significantly exceeding those in other foods. This may be attributed to differences in moisture content, root absorption mechanisms, and processing methods. The concentration pattern of REEs in all samples occurred in the following order: cerium > lanthanum > yttrium > neodymium > neodymium > scandium > praseodymium > gadolinium > dysprosium. The light REEs/heavy REEs (HREEs) ratio was consistently > 2 but remained lower than the ratios observed in the soil and sediments, indicating a potential risk of HREE enrichment. Dietary exposure assessments revealed that the total REE intake among Zhejiang residents was below the established safety threshold (51.3 µg/kg BW/day), with children experiencing the highest exposure (3.71 µg/kg BW/day), primarily due to their lower body weight. In the assessment of individual rare earth elements, Ce exposure in children aged ≤ 6 years exceeded the toxicological reference value. However, this threshold was established based on studies in pregnant and lactating populations and might not be directly applicable to young children. Therefore, overall dietary exposure to individual REEs remains within safe limits. REE exposure from tea consumption did not pose a health risk, even for habitual tea drinkers. These findings underscore the importance of continuous monitoring of REE accumulation in food and additional research on the potential long-term health effects, even though the current exposure levels of REEs are below the established safety limit. This is especially important considering the bioaccumulative nature of REEs and the limited paucity of toxicological data, particularly in vulnerable populations.